Barbarous Custom: discursively deconstructing The Prevent Duty - Kate Brooks (Educational Futures)
The contentious anti-terrorism programme for education, The Prevent Duty, designed to enable teachers, lecturers and youth workers to intervene if young people are ‘at risk’ of radicalisation, remains subject to criticism, most recently that it creates a ‘culture of fear’ in education. This article offers a critical discourse analysis of The Prevent Duty, arguing that rather than critique it for its ‘cultural ignorance’, the programme’s central failure is its ethnocentric and problematic reworking of new subjectivities from old pathologies. Taking a Foucauldian perspective in order to identify key themes as discursive repertoires, the article notes how similar repertoires appear in markedly similar ways at moments of perceived national instability. Thus, whilst Britain may well be facing new threats as a nation, the ways in which the threats are defined, conceptualised and supposedly tackled through the programme are not new, but examples of recurring, contradictory and paternalist discourses. These discursive repertoires take the form of – at best- ethnocentric benevolence towards an irrational Other, whilst an imagined community of an unproblematic ‘us’ is set against a reductive and emotive model of radicalisation and risk. Identifying links between British colonial writing and other forms of panoptic, discursive formations, the article concludes with the observation that these repertoires appear to be moving from a paternalist ‘politics of pity’ to a more punitive perspective.